Dutch Colonial Government Intervention in Islamic Judiciary in Indonesia and Its Impact on the Authority of the Pengadilan Agama - Nurul Islamiah; Supardin S; Muh. Rusdi T (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article discusses the intervention of the Dutch colonial government in Islamic judiciary institutions in Indonesia and its impact on the authority of religious courts. Prior to the colonial period, Islamic courts had developed within Islamic kingdoms and possessed broad authority in resolving religious and social disputes. However, the arrival of the Dutch colonial administration brought significant changes to the legal system in Indonesia through colonial legal policies aimed at controlling indigenous society, including Muslims. This study employs a normative legal research method with a historical approach by examining literature, colonial regulations, and various scholarly sources related to the development of Islamic courts during the Dutch East Indies period. The findings indicate that the colonial government did not directly abolish Islamic courts, but gradually restricted their authority through various policies and regulations. Islamic courts, which previously held extensive authority, were later limited to certain matters such as marriage, divorce, reconciliation, and inheritance. This intervention was influenced by colonial legal politics and the receptie theory, which placed customary law above Islamic law. Nevertheless, Islamic judiciary institutions survived and became one of the important foundations for the development of the religious court system in post-independence Indonesia.